Axonal excitability changes and acute symptoms of oxaliplatin treatment: In vivo evidence for slowed sodium channel inactivation. Issue 3 (March 2018) - Heide, Rikke; Bostock, Hugh; Ventzel, Lise; Grafe, Peter; Bergmans, Joseph; Fuglsang-Frederiksen, Anders; Finnerup, Nanna B.; Tankisi, Hatice
Highlights: Symptoms after oxaliplatin infusion correlate with nerve excitability findings. Oxaliplatin induces a slowing of sodium channel inactivation in motor nerve fibres. Motor nerve superexcitability may be a good biomarker of acute oxaliplatin neurotoxicity. Abstract: Objective: Neurotoxicity is the most frequent dose-limiting side effect of the anti-cancer agent oxaliplatin, but the mechanisms are not well understood. This study used nerve excitability testing to investigate the pathophysiology of the acute neurotoxicity. Methods: Questionnaires, quantitative sensory tests, nerve conduction studies and nerve excitability testing were undertaken in 12 patients with high-risk colorectal cancer treated with adjuvant oxaliplatin and in 16 sex- and age-matched healthy controls. Examinations were performed twice for patients: once within 3 days after oxaliplatin treatment (post-infusion examination) and once shortly before the following treatment (recovery examination). Results: The most frequent post-infusion symptoms were tingling paresthesias and cold allodynia. The most prominent nerve excitability change was decreased superexcitability of motor axons which correlated with the average intensity of abnormal sensations (Spearman Rho = 0.80, p < .01). The motor nerve excitability changes were well modeled by a slowing of sodium channel inactivation, and were proportional to dose/m 2 with a half-life of about 10d. Conclusions: Oxaliplatin induces reversible slowing of sodium channel inactivation in motor axons, and these changes are closely related to the reversible cold allodynia. However, further studies are required due to small sample size in this study. Significance: Nerve excitability data provide an index of sodium channel dysfunction: an objective biomarker of acute oxaliplatin neurotoxicity.